The Geomorphology of Glaciomarine Sediments in a High Arctic Fiord - Bednarski, Jan (Géographie physique et Quaternaire, 1988)
ABSTRACTA general geomorphic model describing marine transgressions and regressions under non-glacial conditions is applied to the glacial environment. The general model recognizes two variables: i) the rate of relative sea level change, and ii) the rate of sedimentation at the coastline. The interaction of the two variables determines the nature of transgression or regression at a particular shoreline. In glaciated areas both sedimentation rates and relative sea level changes are controlled mainly by glacioclimatic responses of the ice. This is best illustrated along arctic coastlines where glacioisostatic loading caused extensive marine inundations during, and immediately after, the last glaciation. Subsequent emergence in the early Holocene has exposed extensive raised marine deposits. Clements Markham Inlet, on the northernmost coast of Ellesmere Island, Northwest Territories, contains raised marine deposits which have a definite spatial and sequential distribution related to the glacial history. The general geomorphic model is used to explain the distribution and geomorphology of this sediment. As the glacial cycle proceeds the balance between fluxes of sediment input and rate of sea level rise or fall will have a direct bearing on the type of stratigraphie sequence found in a particular area.